2012
DOI: 10.1093/infdis/jis744
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Dengue Virus Challenge of Human Subjects Previously Vaccinated With Live Attenuated Tetravalent Dengue Vaccines

Abstract: Vaccination with TDV induced variable protection against subcutaneous challenge. DENV-3 experimental challenge was associated with transient but marked elevations of transaminases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…[44][45][46] The work of Sabin indicates that human challenge studies can be conducted safely. None of the 243 subjects showed development of severe dengue.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] The work of Sabin indicates that human challenge studies can be conducted safely. None of the 243 subjects showed development of severe dengue.…”
Section: Discussionmentioning
confidence: 99%
“…These studies also enabled investigators to characterize the clinical and laboratory manifestations of a primary dengue infection. In addition, early candidate dengue vaccines were developed and/or evaluated for protection against challenge or developed for use as challenge viruses [26][27][28][29][30]. Prior to the ability to culture the virus, investigators transmitted dengue from one infected person to another using the natural Aedes mosquito vector [25,26].…”
Section: History Of the Dengue Human Infection Model (Dhim)mentioning
confidence: 99%
“…The ideal DHIM would induce objective, reproducible endpoints with sufficient frequency that statistically significant protection could be determined using a smaller number of subjects. In addition, if the model could produce these endpoints without inducing significant illness, the risk to volunteers could be minimized and the studies may be performed [25] 1931 80 USA Vector identification, culture, infectious dose, pathology Sabin [4] 1952 >216 USA Immunology, Passaged LADV Wisseman [28] 1966 4 USA Passaged LADV challenge studies Fujita [47] 1969 10 Japan Effects of administration of DENV-1 and YF together Statler [44] 2008 12 USA Evaluation of DENV challenge strains, Ultrasound-based diagnostics Mammen [30] 2014 Sun [29] 2013 16 USA LATV-challenge study EIP, extrinsic incubation period; LADV, live attenuated dengue vaccine; LATV, live attenuated tetravalent vaccine.…”
Section: Dengue Infection Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in this study and previous work, AGMs are proving to be a useful model for dengue vaccine development (17,46). Recent studies in humans have shown other dengue vaccines unable to fully protect against challenge from all 4 DENV serotypes despite previous promising studies in rhesus macaques (6,12,45,(47)(48)(49)(50)(51)(52)(53). Additionally, investigations have shown that AGMs model certain human diseases better than macaques (46,(54)(55)(56).…”
Section: Discussionmentioning
confidence: 58%